2019
DOI: 10.1136/annrheumdis-2019-215313
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and time trends of joint surgery in patients with psoriatic arthritis: a register-based time series and cohort study from Denmark

Abstract: ObjectiveTo investigate time-trends and cumulative incidence of joint surgery among patients with psoriatic arthritis (PsA) compared with the general population.MethodsIn this nationwide register-based cohort study, The Danish National Patient Registry was used to identify incident PsA patients. The 5-year incidence rates (IR) and incidence rate ratios (IRR) of joint surgery were calculated in four calendar-period defined cohorts. Each patient was matched with ten non-PsA individuals from the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(29 reference statements)
0
9
0
2
Order By: Relevance
“…Surgical procedures have been coded in DNPR according to the Nordic Medico-Statistical Committee (NOMESCO) system since 1996. 30 Previous studies have shown that data on surgical procedures in DNPR is valid. [31][32][33] The results of this study indicate that there is almost perfect agreement between GLA:D and registry-based data on the knee and hip replacement surgery at baseline and followup.…”
Section: Surgery and Imagingmentioning
confidence: 99%
“…Surgical procedures have been coded in DNPR according to the Nordic Medico-Statistical Committee (NOMESCO) system since 1996. 30 Previous studies have shown that data on surgical procedures in DNPR is valid. [31][32][33] The results of this study indicate that there is almost perfect agreement between GLA:D and registry-based data on the knee and hip replacement surgery at baseline and followup.…”
Section: Surgery and Imagingmentioning
confidence: 99%
“…Since the introduction of bDMARD therapies in the early 2000s, surgical interventions have fortunately decreased, not only in Germany but also in many other countries [49][50][51][52][53]. Nevertheless, surgical interventions are still more frequent in patients with inflammatory rheumatic diseases than in the healthy population [54]. Complications following surgery, on the other hand, appear to be declining over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, no reduction in the OS trend was found in those studies, in which only patients with PsA were analysed. Guldberg-Møller et al 17 analysed 11 960 patienst with PsA (mean age 50 years; 57% female) from 1996 to 2017. The IRR of any joint surgery was two times as high for patients with PsA as for the general population across all the calendar periods analysed.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Abraham et al (between 2002 and 2013) revealed an increasing trend towards knee arthroplasties in patients with spondylitis in a sample obtained in their nationwide inpatient sample 15. Other studies found a decreasing trend in hip arthroplasties for patients with AS,16 although another study on PsA did not find a decreasing trend in arthroplasties 17. As for other types of SpA (eg, SpA-IBD and ReA), studies are manifestly scarce.…”
Section: Introductionmentioning
confidence: 99%